Initial clinical application of tissue pH neutralization after esophageal button battery removal in children. (5th March 2019) - Jatana, Kris R.; Barron, Christine L.; Jacobs, Ian N.
Abstract : Objectives/Hypothesis: Pediatric esophageal button battery (BB) injuries can progress even after removal and continue to be a significant source of morbidity and mortality. The objective in this case series is to present initial safety data for the human application of intraoperative tissue pH neutralization using 0.25% acetic acid irrigation after BB removal. Study Design: Retrospective case series. Methods: Pediatric patients who underwent rigid esophagoscopy for BB removal between October 2016 and December 2017 and who had the injury site irrigated with 120 to 150 mL sterile 0.25% acetic acid (pH = 3) were included in the study. Outcome measures included visual tissue appearance after irrigation, immediate or delayed esophageal perforation, and evidence of eventual esophageal stricture formation. Results: Six pediatric patients (aged 19 months–10 years) had a 3 V lithium BB lodged in the esophagus for 2 to 18 hours and had irrigation of the esophageal injury site with sterile 0.25% acetic acid in the operating room after BB removal. None of the patients showed any evidence of thermal tissue injury. By surgeon assessment, all cases had improved visual esophageal tissue appearance. Neither immediate post‐operative or delayed onset esophageal perforation nor eventual stricture development were seen. Conclusions: Esophageal irrigation in the operating room with sterile 0.25% acetic acid after BB removal, to neutralize the highly alkaline tissue microenvironment (pH 10–13) was safe and resulted in improved visual mucosal appearance. This immediate tissue pH neutralization may help halt the progression of liquefactive necrosis by immediately bringing tissue pH to physiologic range. This post‐removal irrigation technique is recommended by current National Capital Poison Center BB guidelines. Level of Evidence: 4 Laryngoscope, 129:1772–1776, 2019